2002
DOI: 10.1063/1.1495872
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an atmospheric microwave-induced plasma generated in ambient air by an argon discharge excited in an open-ended dielectric discharge tube

Abstract: Parametric observations on an atmospheric-pressure plasma sustained in ambient air by an argon discharge excited by 2.45 GHz microwaves in an open-ended dielectric discharge tube are reported. Microwave power, discharge tube dimensions, and argon flow rate were the major operating parameters. Three distinctive plasma regions were observed: plasma filaments exiting from the discharge tube, converging point of these filaments, and a plasma flame. At the filament-converging point, argon atom excitation temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 25 publications
4
59
1
Order By: Relevance
“…According to the experimental results obtained by different authors, these conditions are often found in microwave discharges at atmospheric pressure. 2,3 Thus, García et al 3 obtained radially averaged measurements of the gas temperature, excitation temperature, and electron densities in an argon capillary surface-wave plasma at atmospheric pressure. Their axial results show electron densities in the range of 10 −20 m −3 , gas temperatures of 1300 K, and excitation temperatures ranging from 0.7 to 0.3 eV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the experimental results obtained by different authors, these conditions are often found in microwave discharges at atmospheric pressure. 2,3 Thus, García et al 3 obtained radially averaged measurements of the gas temperature, excitation temperature, and electron densities in an argon capillary surface-wave plasma at atmospheric pressure. Their axial results show electron densities in the range of 10 −20 m −3 , gas temperatures of 1300 K, and excitation temperatures ranging from 0.7 to 0.3 eV.…”
Section: Discussionmentioning
confidence: 99%
“…These results could explain the low values of electron temperatures reported in some works on argon microwave discharges at atmospheric pressure. 2,3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, typical MW plasma torch operated at 2.45 GHz produced maximum temperature of 6 000 K at atmospheric pressure while operated by 2 000 W power. [16] For Ar MW plasma at 1 atm with power range of 650-950 W, the thermocouple and optical emission spectroscopy showed temperature of 1 030-2 200 K. [17] In other literature for up to 600 W MW power, lower temperature plasma zone of 500-1 000 K at low pressure near the discharge volume have been estimated. [1] However, regarding our experimental set-up running with maximum MW power of 300 W, regarding ref.…”
Section: Pre-estimation To Experiments (Simulation Of Compositions Ofmentioning
confidence: 99%